Oxygen Reduction Reaction Activity of Platinum Thin Films with Different Densities. (24th August 2017) - Ergul, Busra; Begum, Mahbuba; Kariuki, Nancy; Myers, Deborah J; Karabacak, Tansel
Abstract : Platinum thin films with different densities were grown on glassy carbon electrodes by high pressure sputtering deposition and evaluated as oxygen reduction reaction catalysts for polymer electrolyte fuel cells using cyclic voltammetry and rotating disk electrode techniques in aqueous perchloric acid electrolyte. The electrochemically active surface area, ORR mass activity (MA) and specific activity (SA) of the thin film electrodes were obtained. MA and SA were found to be higher for low-density films than for high-density film.